IN SITU SHRIMP U-PB DATING OF MONAZITE INTEGRATED WITH PETROLOGY AND TEXTURES: DOES BULK COMPOSITION CONTROL WHETHER MONAZITE FORMS IN LOW-CA PELITIC ROCKS DURING AMPHIBOLITE FACIES METAMORPHISM? - Rasmussen B.; Muhling J.R.; Fletcher I.R.; Wingate M.T.D. (My University, 2006)
Bulk composition and specific reaction history among common silicate minerals have been proposed as controls on monazite growth in metapelitic rocks during amphibolite facies metamorphism. It has also been implied that monazite that formed during greenschist facies metamorphism may be preserved unchanged under upper amphibolite facies conditions. If correct, this would make the interpretation of monazite ages in polymetamorphic rocks exceedingly difficult, because isotopic dates could vary significantly in rocks that have experienced identical metamorphic conditions but differ only slightly in whole-rock composition. Low-Ca pelitic schists from the Mount Barren Group in southwestern Australia display a range of whole-rock compositions in AFM space and different peak mineral assemblages resulting from amphibolite facies metamorphism (?8 kb, 650 °C). In this study, we test whether bulk composition controls the formation of monazite through geochronology and textural evidence linking monazite growth with deformation and peak metamorphism. X-ray element mapping of monazite from the metapelitic rocks reveals concentric zoning in many grains with compositionally distinct cores and rims. In situ SHRIMP U-Pb geochronology of monazite yields two 207Pb/206Pb age populations. The cores, and texturally early monazite, give an age of 1209 ? 10 Ma, interpreted to record prograde metamorphism, whereas the rims and "late" monazite define a single population of 1186 ? 6 Ma, which is considered the likely age of peak thermal metamorphism. The growth of monazite was widespread in low-Ca pelitic schists representing a broad range of compositions in AFM space, indicating that variations in bulk composition in AFM space did not control the formation of monazite during amphibolite facies metamorphism in the Mount Barren Group. ? 2006 Elsevier Inc. All rights reserved.
Keywords: AMPHIBOLITE FACIES; GEOCHRONOLOGY; METAMORPHISM; MONAZITE; PELITE; URANIUM-LEAD DATING